2018
DOI: 10.1039/c8cc07271j
|View full text |Cite
|
Sign up to set email alerts
|

3-Homoacyl coumarin: an all carbon 1,3-dipole for enantioselective concerted (3+2) cycloaddition

Abstract: A stereoselective concerted (3+2) cycloaddition is demonstrated from 3-homoacyl coumarins and alkylidene indandiones, resulting in fused spirocyclopentanes bearing four contiguous stereocenters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In recent years, a readily accessible material i.e. 2-arylidene-1,3-indandiones 24 has started gaining importance in the field of phosphine catalysed annulations. 25 A regioselective [4+2] 26 cyclisation between 2-arylidene-1,3-indandiones and γ-substituted allenoates was carried out explicitly by Huang and co-workers towards synthesis of spiro[4.5]dec-6-ene skeletons as δ-adduct (eqn (a), Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a readily accessible material i.e. 2-arylidene-1,3-indandiones 24 has started gaining importance in the field of phosphine catalysed annulations. 25 A regioselective [4+2] 26 cyclisation between 2-arylidene-1,3-indandiones and γ-substituted allenoates was carried out explicitly by Huang and co-workers towards synthesis of spiro[4.5]dec-6-ene skeletons as δ-adduct (eqn (a), Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have found that 3-homoacylcoumarin as 1,3-dipole precursor proceeds the stepwise (3 + 2) cycloaddition reaction with unsymmetrical alkylidene oxindole electrophiles whereas a concerted (3 + 2) cycloaddition has been reported with symmetric indandione alkylidenes. [8] Further studies regarding the application of 3-homoacylcoumarin in other organocatalytic reactions are underway in our laboratory.…”
Section: Communications Ascwiley-vchdementioning
confidence: 99%
“…[7] In 2018, we reported a quinine-derived bifunctional thioureacatalyzed concerted (3 + 2) cycloaddition reaction for the highly stereoselective synthesis of five membered coumarin/indanedione-fused spirocyclopentanes bearing four contiguous stereocenters. [8] Inspired from our previous work, we were keen on developing a (3 + 2) cycloaddition reaction for spirooxindole scaffolds, utilizing 3-homoacylcoumarin and alkylidene oxindole electrophiles. The supposed cycloaddition reaction would lead to less explored hybrid scaffolds that comprise both the privileged moieties and also bear five contiguous stereocenters, including a quaternary spiro-stereocenter.…”
mentioning
confidence: 99%
“…A stereoselective [3 + 2] cycloaddition with indandione alkylidenes 103 and 3-homoacylcoumarin 70 as the 1,3-dipole precursor, to generate a series of coumarin/indandione-fused spirocyclopentanes 104 bearing four contiguous stereogenic centers, was described by Chen et al [ 68 ]. This transformation was catalyzed by a cinchona-thiourea derivative 105 furnishing the spiro compounds with good to high yield and enantioselectivity ( Scheme 33 ).…”
Section: Reviewmentioning
confidence: 99%